How Do People Evaluate Foreign Aid To 'Nasty' Regimes?. Issue 1 (28th February 2018) - Heinrich, Tobias; Kobayashi, Yoshiharu
Abstract : Recent theories of foreign aid assume that moral motives drive voters' preferences about foreign aid. However, little is known about how moral concerns interact with the widely accepted instrumental goals that aid serves. Moreover, what effects does this interplay have on preferences over policy actions? This article assesses these questions using a survey experiment in which respondents evaluate foreign aid policies toward nasty recipient regimes (those that violate human rights, rig elections, crack down on media, etc.). The results indicate that the public does have a strong aversion to providing aid to nasty recipient regimes, but that it also appreciates the instrumental benefits that aid helps acquire. Contrary to a mainstay assertion in the literature, the study finds that moral aversion can largely be reversed if the donor government engages more with the nasty country. These findings call into question the micro-foundations of recent theories of foreign aid, and produce several implications for the aid literature.